Glyphosate bioremediation using a newly isolated Bacillus albus strain F9D: mechanisms and kinetic studies - Wen-Juan Chen; Mingqiu Liu; Shao-Fang Chen; Yuming Zhang; Haoran Song; Maman Hassan Abdoulahi; Kalpana Bhatt; Sandhya Mishra; Mohamed A. Ghorab; Wenping Zhang; Shaohua Chen (Microbial Cell Factories)
Abstract Glyphosate is widely used as an herbicide around the world. The extensive application of glyphosate, however, has serious adverse effects on living systems. Therefore, the elimination of residual glyphosate pollution has become an urgent issue worldwide. In the present study, a novel bacterial strain named F9D was identified as Bacillus albus, based on its physio-biochemical characteristics and 16 S rDNA analysis. This strain can completely degrade glyphosate (400 mg/L) within 5 days. An effective, rapid, and stable detection method for glyphosate and aminomethylphosphonic acid (AMPA) was developed using ultra-performance liquid chromatography–tandem mass spectrometry technology (UPLC-MS/MS). The degradability of glyphosate by the degrading strain F9D was optimized, considering various conditions, as follows: initial pH (5–9), incubation temperature (20–40℃), glyphosate concentration (50–800 mg/L), and inoculation amount (1–5%). The strain also demonstrated strong degradation ability in soil and water–sediment systems: 78.1% glyphosate (400 mg/kg) and 83.2% glyphosate (200 mg/kg), respectively, degraded in soil and water–sediment systems within 5 days of incubation. Furthermore, the F9D strain is capable of degrading 50–800 mg/L of glyphosate and AMPA under various treatments. Hence, the notable ability of B. albus strain F9D to degrade glyphosate makes it a highly promising candidate for the removal of this emerging contaminant from the environment on a large scale.